Stalking w Japonii – problematyka prawna ustawy Sutōkā Kisei Hō z 2000 roku - Jelonek, Barbara (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2018)
Stalking in Japan is now well common phenomenon. In 2000 was introduced in Japan first legal regulation against stalking (jap. Sutōkā Kōi Nado no Kisei Nado ni Kansuru Hōritsu). In this article author would like to present the causes and the legislation proces of nascency this legal act, the main legal examples of stalking cases (case study e.g. Shiori Ino, Gota Tsutsui, Mayu Tomita, Saaya Suzuki, Ikumi Yoshimatsu), and discuss about actual law regulations and latest revision of these provisions from 2013 and 2017
Keywords: stalking; Japan; law; tsukimatou; Sutōkā Kisei Hō; Shiori Ino; Mayu Tomita; Gota Tsutsui; Saaya Suzuki; Ikumi Yoshimatsu